Evaluating the Impact of the Post-2008 Employment Subsidy Program in Turkey - Binnur Balkan; Yusuf Soner Baskaya; Semih Tumen (Institute for the Study of Labor (IZA), 2016)
This paper investigates the employment effects of a targeted subsidy scheme implemented in Turkey following the 2008 crisis. The Turkish government started a subsidy program in 2008 to generate new employment for younger men and all women, which are the relatively disadvantaged groups in the Turkish labor markets. The program puts men of age 18-29 and all women into the treatment group, while men of age 30 and above are placed into the control group. We use a nationally representative micro-level dataset and a difference-in-differences approach to estimate the causal effect of this program. On aggregate, the subsidy program seems to be ineffective in increasing the employment probabilities of those individuals in the target group. However, when heterogeneity is accounted for by dividing the treatment group into several sub-groups, we observe that the program has been notably effective on some of those sub-groups. In particular, the increase in employment probability is high for older women, while a weaker positive effect is observed for younger women and almost no effect is detected for younger men. The effect on older women is subject to further heterogeneity: the program has increased the employment probabilities of low-educated and/or low-skill older women rather than the high-educated and/or high-skill ones.
Keywords: C21; H24; J21; J68; 330; employment subsidies; treatment effects; difference-in-differences; Turkish micro data